TRANSACTION COST MANAGEMENT STRATEGIES FOR SMALL-SCALE PPP PROJECT CASE STUDY OF MADIUN CITY STREET LIGHTING - Prabowo, Sakti; Suhendra, Maman; Dinardjito, Agung (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Small-scale Public-Private Partnership (PPP) projects offer local governments an opportunity to enhance regional development. However, these schemes are often perceived to incur higher transaction costs compared to conventional PPP projects. This study seeks to identify the factors contributing to increased transaction costs in small-scale PPP projects, using the Madiun City Street Lighting PPP project as a case study. Employing a qualitative research methodology by studying the related literature and interviewing the consultant of the project, this study gathers pertinent information regarding the transaction costs associated with the Madiun City Street Lighting PPP project, which serves as a pioneering example of small-scale PPP initiatives in Indonesia. This paper analyzes that project value, complexity process, coordination, parties’ capacity, opportunistic behavior, and contract change put higher transaction cost on small-scale PPP project proportionally. However, the analysis reveals that the complexity of coordination between local government authorities and the Regional House of Representatives (DPRD) can be effectively managed by the contracting agency (PJPK) of the Madiun City Street Lighting PPP project.